Notes and Comments on Robert's Rules, Fourth Edition - Slaughter, Jim, 1964- (Book collections on Project MUSE., 2012)
While Robert's Rules of Order has long been the standard guide to parliamentary procedure, many readers find the manual too daunting and complex to utilize its full potential. In this book, the authors guide readers through the intricate pathways of the latest edition of Robert's Rules, transforming the often intimidating parliamentary guidebook into an easy-to-use tool.